Prayer and Character Building as Core Predictors of Spiritual Growth: Lessons from Christian Higher Education for Global Well-being - Elon, Yunus; Pardosi, Milton Thorman (Jurnal Iman dan Spiritualitas, 2025)
The world today faces multiple crises—ecological, social, and moral—that call for the emergence of a generation with a strong spiritual foundation, resilience, and clarity of values in every aspect of leadership. This study explored six dimensions of spiritual growth—Abide in Christ, Live by God’s Word, Pray in Faith, Fellowship with Believers, Witness to the World, and Minister to Others—within the context of Christian higher education. Data were collected from 132 students at Universitas Advent Indonesia using the Spiritual Growth Assessment Process (LifeWay Christian Resources).  Descriptive analysis revealed that "Pray in Faith" (M = 4.25, SD = 0.59) and "Abide in Christ" (M = 4.33, SD = 0.61) were the strongest practices, whereas "Minister to Others" (M = 3.54, SD = 0.94) indicated lower engagement. Correlation analysis revealed strong associations among the dimensions, with the highest between Witness to the World and Minister to Others (r = 0.881, p < 0.001). Multiple regression demonstrated that Minister to Others (β = 0.31, p < 0.001), Pray in Faith (β = 0.25, p = 0.01), and Live by God’s Word (β = 0.21, p = 0.03) significantly predicted Fellowship with Believers. The model accounted for 62% of the variance (R² = 0.62, p < 0.001). These findings confirm that prayer and moral formation are pivotal to spiritual growth, emphasizing the transformative role of Christian higher education in shaping graduates who unite intellectual competence with moral integrity and spiritual maturity.